2021
DOI: 10.3390/ijerph18041955
|View full text |Cite
|
Sign up to set email alerts
|

Self-Injurious Behavior in Community Youth

Abstract: The rapid increase of self-injurious behavior among Korean adolescents, and its reckless spread on social media, has driven the necessity to study this behavior. The present study investigates the characteristics of self-injurious behavior among adolescents in local communities, and the psychological factors affecting such behavior. Questionnaires were administered to 516 sixth graders in elementary school and first to third graders in middle school of both genders, nationwide. They measured the prevalence and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 74 publications
(120 reference statements)
0
7
1
2
Order By: Relevance
“…It is possible that adolescents rarely opt to swallow drugs/toxic substances/chemicals because of their preference for sensory stimulation: more physically involved attempts at self-harm may stimulate the senses more quickly and speed up the reactionary feeling of control. Although another study in 516 Korean adolescents found the incidence of cutting injury was high (19.3%) ( 82 ), the prevalence was only 7.0% in our meta-analysis. This may be related to the difficulty in acquiring dangerous goods in some countries, such as blades and sharp tools, or cutting injury was scary and bloody for most adolescents.…”
Section: Discussioncontrasting
confidence: 74%
“…It is possible that adolescents rarely opt to swallow drugs/toxic substances/chemicals because of their preference for sensory stimulation: more physically involved attempts at self-harm may stimulate the senses more quickly and speed up the reactionary feeling of control. Although another study in 516 Korean adolescents found the incidence of cutting injury was high (19.3%) ( 82 ), the prevalence was only 7.0% in our meta-analysis. This may be related to the difficulty in acquiring dangerous goods in some countries, such as blades and sharp tools, or cutting injury was scary and bloody for most adolescents.…”
Section: Discussioncontrasting
confidence: 74%
“…Como ya se ha demostrado que ALNS al ser un mecanismo de afrontamiento evitativoemocional que alivia un estado perturbador asociado a emociones negativas y en algunas ocasiones vinculado a disociación de ideas e ideas irracionales que en conjunto disminuyen la probabilidad de resolver las dificultades del adolescente y lo envuelven en una esfera de desesperanza y depresión (Son et al, 2021), según los datos obtenidos en este estudio, la mitad de la población podría mejorar sus estrategias de enfrentamiento y disminuir el uso de ALNS tan solo motivando a los padres para mejorar la comunicación con los hijos y monitorear el uso del internet manteniéndolo bajo control, evitando el uso adictivo.…”
Section: Discussionunclassified
“…In particular, self-harm among adolescents has been recognized as a significant public mental health issue worldwide, as it tends to begin in adolescence and be recurrent (Rahman et al, 2021). A recent study in South Korea reported that a high percentage of adolescents (more than 30%) in the general community engaged in self-injurious behavior (Son et al, 2021).…”
Section: Self-harm In Sexually Abused Adolescentsmentioning
confidence: 99%